Investigation on bluff-body and swirl stabilized flames near lean blowoff with PIV/PLIF measurements and LES modelling - Guo, Shilong; Wang, Jinhua; Zhang, Weijie; Lin, Bingxuan; Wu, Yun; Yu, Senbin; Li, Guohua; Hu, Zhiyun; Huang, Zuohua (Applied thermal engineering, 2019)
•PIV/PLIF simultaneous measurement and LES on swirl flames were conducted.•The non-dynamic formulation cannot predict the near-blowoff flame reasonably.•PVC exists in the near-blowoff flame while disappears under stable condition.•The heat loss, excess strain and TKE at flame attachment contribute to lift-off. Lean premixed combustion (LPC) is a promising technology for low-NOx emission, while it increases the risk of blowoff at the same time. Experiments and Large Eddy Simulations (LES) on swirl stratified lean-premixed CH4/air flames were performed to study the differences between the stable and near blowoff flame. The flow fields and instantaneous flame structures were measured by simultaneous Particle Image Velocimetry (PIV) and Planar Laser Induced Fluorescence (OH-PLIF). The Thickened Flame (TF) model coupled with a two-step reduced chemical mechanism was used in LES modelling. The non-dynamic formulation of sub-grid flame wrinkling model is performed well for stable condition while it cannot predict the near lean blowoff flame reasonable. Compared with the stable flame, several significant differences can be observed in the near lean blowoff flame. The height of high-temperature-zone is relatively low and the heat loss of flame attachment can be easily enhanced by the low temperature spot induced by flame-vortex interaction. The flame attachment is subject to higher excess strain rate and turbulence fluctuation. Meanwhile, a Processing Vortex Core (PVC) appears downstream of the centerline. It is concluded that lean blowoff is the result of interactions between the fuel/air mixture ignition, PVC instability and flame attachment lift-off.